FAKTOR-FAKTOR YANG MEMENGARUHI FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR - Vincentsius Alfred Stephen; Nurainun Bangun (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this study is to empirically prove the effect of audit committees, leverage, and sales growth on financial distress in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. The sample used in this research is as many as 90 sample data selected by purposive sampling method. The results of this study indicate that all independent variables can simultaneously predict financial distress (ICR)as evidenced by the results of the F test. From the results of the T test, it is clear that audit committee size has no significant positive effect on financial distress, leverage (DAR) has a significant negative effect on financial distress, and sales growth does not have a significant negative effect on financial distress.